Analisa Koordinasi Relay Proteksi OCR dan Recloser Pada Sistem Distribusi 20kV - Prastyo, Agung; Wati, Trisna (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
Based on data from the PT PLN Bojonegoro main substation, there were 3 disruptions a month, which caused several distribution feeders to trip. One of the causes of a trip in this protection system is due to an error in the coordination settings between the Over Current Relay (OCR) and the recloser. The aim of this research is to review the value of the OCR and recloser settings on the 20 kV distribution channel at the Bojonegoro Main Substation to maximize how the protection equipment works in the event of a disturbance. The calculation results for the recloser are 0.07 seconds, the incoming OCR is 0.27 seconds, and the outgoing OCR is 0.11 seconds. Meanwhile, the existing TMS OCR and recloser values are 0.1 seconds, the incoming OCR is 0.25 and the outgoing OCR is 0.2 seconds. . Comparison of the TMS OCR incoming, OCR Outgoing, and recloser value settings has a difference of 0.03 seconds, 0.0.02 seconds, and 0.09 seconds.